2010
DOI: 10.1002/minf.201000096
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Molecular Selectivity and Structure Generation for Selective Dopamine Inhibitors

Abstract: Activity landscapes were used in combination with atom colourings for the visualization of molecular selectivity. Multiple inhibitory activities in the dopamine family were selected in order to derive its molecular selectivity. All molecular structures were mapped in 2D chemical space by preserving the relative distance between any pair of molecules using multidimensional scaling. The values for the inhibitory activity against each dopamine isoenzyme (D2, D3, and D4) were added independently to the data points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In this work, feature importance of each ECFP bit is derived from the random forest (RF) after the five-fold cross-validation as mentioned above, and feature importance will be automatically linked to the corresponding fingerprint bit “1” and structural feature in our e-Bitter program. However, the feature importance from RF can only tell us whether these features are vital to the bitter/bitterless classification, but cannot inform us whether each ECFP bit “1” in a compound positively or negatively influences the bitterness, which can be described by the concept “feature partial derivative.” (Hasegawa et al, 2010 ; Marcou et al, 2012 ; Polishchuk, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, feature importance of each ECFP bit is derived from the random forest (RF) after the five-fold cross-validation as mentioned above, and feature importance will be automatically linked to the corresponding fingerprint bit “1” and structural feature in our e-Bitter program. However, the feature importance from RF can only tell us whether these features are vital to the bitter/bitterless classification, but cannot inform us whether each ECFP bit “1” in a compound positively or negatively influences the bitterness, which can be described by the concept “feature partial derivative.” (Hasegawa et al, 2010 ; Marcou et al, 2012 ; Polishchuk, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The feature partial derivative, exactly defined by Equation (8) and Hasegawa et al ( 2010 ) is firstly proposed in the work of Byvatov and Schneider ( 2004 ) and is systematically reviewed in the work of Polishchuk ( 2017 ). To derive the feature partial derivative of each ECFP bit, the backward finite difference approach is adopted and briefly described as follows (Hasegawa et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marcou et al [78] as well as Hasegawa et al [79] have both recently reported methodologies to accomplish this task (also see references therein). In both methods, the idea is to perturbate an atomic feature systematically and evaluate the extent to which the perturbation causes a change in predicted endpoint value.…”
Section: Special Issue Chemogenomicsmentioning
confidence: 97%
“…While some research has focused on predicting biological activity based on these data, the results have not provided insight on characteristic structures [4,5]. Rough set and activity landscape methods have provided useful suggestions as to the active substructure, but the number of molecules in the datasets was limited [6,7]. …”
Section: Introductionmentioning
confidence: 99%